Enhancement of Transient Stability in a Grid-Connected Wind Power Plant Utilizing PI-FL Controller - et. al., Dr. KamalaMoorthy N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposed a blend of corresponding PIC and FLC for controlling the pitch angle of wind turbine connected to grid. Initially, conventional control methodology is employed to design the PI controller and later on, the concept of fuzzy logic methodology is adapted to analyze the gains of proportional integral controller. Due to versatility of fuzzy logic controller and rugged structure, sturdy nature of proportional integral controller are clubbed together, it provides a virtuous stagnant and dynamic outcomes. The proposed novel technique can be assessed by considering various disturbances such as short circuit network fault. The reenactment after effects of proposed controller is contrasted with proportional integral controller and FLC. From the findings it is shown that the proposed methodology could improve stability even the wind farm is subjected to different operating conditions. Moreover, a performance index in terms of absolute maximum deviations is defined in order to evaluate the adequacy of the proposed controller.